The Maximisation of Profit by a Newspaper - Corden, W. M. (Review of Economic Studies, 1952)
Journal Article The Maximisation of Profit by a Newspaper Get access W. M. Corden W. M. Corden Melbourne, Australia Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 20, Issue 3, 1952, Pages 181–190, https://doi.org/10.2307/2295888 Published: 01 January 1952